Business Development on Penetration of Motor Insurance In India - Devansh Garg; Dr. Jaideep Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This report examines the landscape of motor insurance penetration in India, focusing on business development strategies to enhance coverage. Despite significant market size (estimated at INR 1 trillion in 2024) and projected growth, India faces challenges with low motor insurance penetration, particularly in rural areas, with a large number of vehicles remaining uninsured. Key challenges include low awareness, price sensitivity, high claim ratios, and fraudulent claims. This report explores the current market dynamics, regulatory framework under IRDAI, consumer behavior, and the critical role of technology (Insurtech). It outlines business development strategies focusing on digital transformation, customer- centricity, data analytics, product innovation (like Usage-Based Insurance), and distribution channel optimization to address these challenges and drive increased penetration, aligning with the national goal of 'Insurance for All'.
Keywords: Motor Insurance; Insurance Penetration; Insurtech; IRDAI; Third-Party Liability; Own Damage